Strategic Literacy and Cognitive Restraints in Owner-Managed Enterprises: Overcoming Barriers through AI-Supported Decision-Making - Terpelle, Chris (Global journal of Business and Integral Security, 2026)
Owner-managed enterprises, small enterprises with fewer than 10 employees, are a crucial part of microenterprises worldwide. Still, they often have limited involvement in formal strategic planning due to low strategic literacy and cognitive limitations. These constraints lead to informal, reactive decisionmaking instead of structured, long-term strategies, resulting in suboptimal performance. This study examines how AI-enabled decision-support tools can reduce cognitive barriers and improve strategic literacy among OMEs. Using a mixed-methods approach that combines qualitative interviews with an AI-supported planning prototype, this research explores literacy gaps, identifies key cognitive limitations, and assesses the influence of digital tools on planning behaviors. Findings suggest that AI support shows potential to enhance planning capacity without adding cognitive load. This paper advances strategic management theory by application of the concept of bounded rationality with digital augmentation, offering practical insights for tool design and policy development.